Use and effectiveness of wildlife exits designed for ocelots and other mesocarnivores on a south Texas highway - Sheikh, Zarina N.; Langbein, Jamie E.; Ryer, Kevin; Rahman, Md Saydur; Gabler, Christopher A.; Young, John H.; Kline, Richard J. (Frontiers in Ecology and Evolution, 2023)
Movement is a key component of survival and reproduction, often causing wildlife to cross heavily trafficked highways, resulting in road mortalities by oncoming vehicles. Fencing and crossing structures are commonly regarded as effective mitigation structures to reduce these mortalities. In south Texas, ten wildlife exits (WE) were installed along State Highway 100 in conjunction with existing mitigation structures to provide the U.S. endangered ocelot (Leopardus pardalis), a medium-sized spotted wild cat, a safe option to escape the right-of-way (ROW). The objectives of this study were to determine the effectiveness and species usage, as well as to estimate the percentage of wildlife that crossed back into the habitat via a WE. Camera traps were used for monitoring with one on the roadside and one on the habitat side of each WE and ten at adjacent right-of-way (ROW) sites. Entry and escape rates were calculated to determine where wildlife was entering and exiting the roadway around WE and total number of individuals for each target species was counted for all entries (H-R) and exits (R-H) at any mitigation structure within 200 m of an exit vs. those using a WE. Results showed that ten species: jackrabbit (Lepus californicus), bobcat (Lynx rufus), coyote (Canis latrans), domestic cat (Felis catus), cottontail (Sylvilagus floridanus), skunk (Mephitis mephitis), racoon (Procyon lotor), opossum (Didelphis virginiana), and weasel (Mustela frenata) used a WE to return to the habitat. Coyote and bobcat both increased their use of WE over time with first use by bobcats in 30 days and coyotes taking 180 days. PERMANOVA showed significantly different assemblages of nine target species between the habitat side and all other groups along the roadside. The species assemblage using WE to escape the roadway was also significantly different from those using the WE to enter the roadway. Approximately 43% of bobcats, a surrogate species for the ocelot, used a WE to escape the ROW. Information on the effectiveness of these novel structures will be useful in the development of future WE to optimize the placement and design them in combination with wildlife fences and crossing structures.